(E)-1-(4-Bromophenyl)but-2-en-1-one - Marcel Sonneck; Anke Spannenberg; Sebastian Wohlrab; Tim Peppel (IUCrData)
The title compound, C10H9BrO, consists of a para-substituted bromophenyl core and an unsaturated carbonyl side chain. The angle between the plane through the carbon atoms of the aryl ring and the plane through the carbon atoms of the unsaturated side chain is 29.12 (16)°. The cohesion in the crystal is ensured by π–π stacking and C—H...O interactions.